Basket diplomacy : leadership, alliance-building, and resilience among the Coushatta tribe of Louisiana, 1884-1984 - Bates, Denise E. (University of Nebraska Press, 2020)
"Basket Diplomacy reveals how the Coushatta people made the Bayou Blue settlement their home by embedding themselves into the area's cultural, economic, and political domains"--